Arabic Language Learning Based on Behaviorism Theory at MTs Al-Adli Palembang - Sari, Anisa Fitria; Wasilah, Wasilah; Rohayati, Enok; Assefi, Khaikal Fasya; Huda, Miftahul (JURNAL IJ-ATL, 2025)
Arabic language learning in madrasas has a strategic role in developing communicative skills as well as understanding of Arabic culture inherent in the language. This study aims to analyze the application of behaviorism theory in Arabic language learning in Madrasah Tsanawiah and its contribution to improving student learning outcomes. The background of this study is the need for effective and adaptive learning strategies for student characteristics to improve the quality of Arabic language learning. By focusing on the principles of repetition, intensive practice, and positive reinforcement, behaviorism theory is considered capable of forming systematic and sustainable learning behavior patterns. This study uses a qualitative approach with descriptive methods and collects data through participatory observation, structured interviews with teachers, students, and madrasah leaders, and documentation of learning activities. The findings show that positive reinforcement strategies such as praise and giving small gifts can significantly increase student learning motivation. Meanwhile, the application of repetitive practice (drill) has been shown to strengthen students' long-term memory of Arabic vocabulary and sentence structures. Practically, this study suggests that the application of behaviorist principles in Arabic language learning design can increase students' active involvement and accelerate the process of internalizing the material. The implications of this study indicate that behaviorism can be an effective pedagogical foundation in developing Arabic language learning strategies that are more measurable, applicable, and appropriate to the context of secondary madrasahs.